Effects of antenatal care service utilization on maternal near miss in Gamo Gofa zone, southern Ethiopia: retrospective cohort study - Tayue Tateke Kebede; Wanzahun Godana; Mesfin Mamo Utaile; Yemisirach Berhanu Sebsibe (BMC, 2021)
Abstract Background Antenatal care (ANC) provides an opportunity to prevent, identify and intervene maternal health problems. Maternal near miss (MNM), as an indicator of maternal health, is increasingly gaining global attention to measure these problems. However, little has been done to measure the effect of ANC on MNM in Ethiopia. Therefore, this study is aimed at determining the effect of ANC on MNM and its associated predictors at Gamo Gofa zone, southern Ethiopia. Methods Employing a retrospective cohort study design, 3 years data of 1440 pregnant mothers (480 ANC attendant and 960 non-attendant) were collected from all hospitals in the zone. Taking ANC visit as an exposure variable; we used a pretested checklist to extract relevant information from the study participants' medical records. Characteristics of study participants, their ANC attendance status, MNM rates and associated predictors were determined. Results Twenty-five (5.2%) ANC attendant and seventy-one (7.4%) non-attendant mothers experienced MNM, (X2 = 2,46, df = 2, p = 0.12). The incidence rates were 59.6 (95% CI: 40.6-88.2) and 86.1 (95%CI: 67.3-107.2)/1000 person-years for the ANC attendant and non-attendant mothers, respectively. Mothers who were living in rural areas had higher hazard ratio of experiencing MNM than those who were living in urban areas, with an adjusted hazard ratio (AHR) of 1.68 (95% CI, 1.01, 2.78). Conclusion ANC attendance tended to reduce MNM. However, late initiation and loss to follow-up were higher in the current study. Therefore, on time initiation and consistent utilization of ANC are required.